1995
DOI: 10.1017/s0007485300036051
|View full text |Cite
|
Sign up to set email alerts
|

Field and laboratory evaluation of a sex pheromone trap for the autodissemination of the fungal entomopathogen Zoophthora radicans (Entomophthorales) by the diamondback moth, Plutella xylostella (Lepidoptera: Yponomeutidae)

Abstract: The effectiveness of a sex pheromone trap designed specifically to deliver conidia (infective fungal propagules) of the entomopathogenic fungus Zoophthora radicans Brefeld (Zygomycetes: Entomophthorales) to male Plutella xylostella (Linnaeus) was investigated. In field experiments in the Cameron Highlands of Malaysia, synthetic pheromone lures attracted adult males P. xylostella at all times of the day whereas lures of virgin female moths attracted males only between the hours of dusk and dawn, when females ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…However, Roy et al (2003) found that C. septempunctata inoculated with P. neoaphidis were only able to vector the pathogen within 4 h of inoculation and conidia vectored onto plants by foraging C. septempunctata were only infective up to 24 h post conidia dispersal (Roy et al, 2003). Nonetheless, vectoring is seen as an important form of dispersal and methods of manipulating this in augmentative and conservation biocontrol strategies are being investigated (Furlong et al, 1995;Bird et al, 2004;Ekesi et al, 2005;Down et al, 2009;Baverstock et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…However, Roy et al (2003) found that C. septempunctata inoculated with P. neoaphidis were only able to vector the pathogen within 4 h of inoculation and conidia vectored onto plants by foraging C. septempunctata were only infective up to 24 h post conidia dispersal (Roy et al, 2003). Nonetheless, vectoring is seen as an important form of dispersal and methods of manipulating this in augmentative and conservation biocontrol strategies are being investigated (Furlong et al, 1995;Bird et al, 2004;Ekesi et al, 2005;Down et al, 2009;Baverstock et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that the females became contaminated through mating with contaminated males. The potential of using either artificial sex pheromones or those released from females to lure adult male diamond back moths, P. xylostella, into devices where they were contaminated with Z. radicans has been assessed (Furlong et al 1995;Pell et al 1993). Whereas males only entered devices containing virgin female moths between dusk and dawn (when sex pheromone is naturally released), males entered devices containing synthetic pheromone throughout the day.…”
Section: Assisted Autodisseminationmentioning
confidence: 99%
“…We did not test for altered feeding behaviors among apparently undisturbed aphids in the presence of injured aphids. Studies also are needed to explore the possible synergy between pheromone applications and other control agents (Smart et al 1994, Furlong et al 1995. …”
Section: Resultsmentioning
confidence: 99%